Peran Pancasila dalam Pencegahan dan Pemberantaan Korupsi : Perspektif Hukum Tata Negara - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Inas Alifatus Salma; Athifah Saidah; Khubi Hanan Khoirunisa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Abstract. Pancasila has an important role in various aspects of life, including in efforts to prevent and eradicate corruption. This research aims to examine the role of Pancasila's contribution in the context of constitutional law, especially in terms of integrity and public ethics. Using qualitative research methods and descriptive analysis, this study investigates how Pancasila values such as social justice, fair and civilized humanity, and unity can be integrated into the legal system and state administration to prevent and eradicate corruption. The results of this study show that the use of Pancasila principles in laws and public policies has significant potential to improve transparency and accountability. The study also identifies challenges and barriers to the implementation of Pancasila values and provides recommendations to improve the effectiveness of corruption prevention and eradication in Indonesia. The findings support the argument that Pancasila serves not only as an ideological basis, but also as a practical foundation in building a legal system with integrity.